KECERDASAN EMOSIONAL DOSEN DITINJAU DARI JENIS KELAMIN - Regina Tutik Padmaningrum (Jurnal Kependidikan, 2008)
The aim of the study was to identify 1) the level of emotionalquotient of the lecturers of Mathematics and Natural Sciences basedon their gender at various universities in the Province ofYogyakarta, and 2) the differences in the emotional quotient amongthe lecturers. The study was ex-post facto research. As the researchvariable, emotional quotient was defined as the scores resultingfrom the EQ questionnaire to include self emotion knowing, selfemotion management, self motivation, others emotion knowing, andrelationship construction. The population of the study wasdesignated to be the lecturers of Mathematics and Natural Sciencesat various universities in Yogyakarta Province. The sample of thestudy consisted of 141 lecturers, 72 male and 69 female, taken bypurposive random sampling technique. The instrument was thequestionnaire adapted from relevant references (Ridwan Saptoto:2002). Data were analyzed qualitatively by conversion criteria. EQdifferences were computed statistically by a t-test. Results showedthat the average score of EQ levels of male and female lecturerswere 79.6% (very high criteria) and 78.2% (high criteria). Thedifference (1.4%) was not statistically significant